High Monocyte-to-Lymphocyte Ratio is Associated with Obstructive Sleep Apnea Hypopnea Syndrome - Bao W; Gao J; Fang S; Zhang S; Wan Y (Dove Medical Press, 2024)
Wenyu Bao,* Junkang Gao,* Siyu Fang, Shiwei Zhang, Yufeng Wan Department of Otolaryngology, Head and Neck Surgery, Chaohu Hospital Affiliated to Anhui Medical University, Hefei, 238000, People's Republic of China*These authors contributed equally to this workCorrespondence: Yufeng Wan, Department of Otolaryngology, Head and Neck Surgery, Chaohu Hospital Affiliated to Anhui Medical University, Hefei, 238000, People's Republic of China, Email Wanyufeng135@126.comObjective: This study aims to explore the correlation between serum monocyte-to-lymphocyte ratio (MLR) and other inflammatory parameters with the occurrence of obstructive sleep apnea-hypopnea syndrome (OSAHS) in patients.Methods: This study included 310 patients who underwent polysomnography monitoring at our hospital between January 2021 and January 2023. Routine blood inflammatory parameters and polysomnography (PSG) results were also evaluated. The differences in inflammatory markers between the OSAHS and normal groups were compared, and OSAHS independent related factors were screened.Results: The MLR of OSAHS group was significantly higher than that of control group, and the difference was statistically significant. Multivariate logistic regression analysis suggested that MLR is an independent risk factor for OSAHS.Conclusion: High MLR was correlated with OSAHS. The diagnostic value of MLR was better than that of the other inflammatory parameters.Keywords: obstructive sleep apnea hypopnea syndrome, inflammation, monocyte to lymphocyte ratio, polysomnography